2014
DOI: 10.1128/jvi.03126-13
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Induces the ATM and H2AX DNA Damage Response Early during De Novo Infection of Primary Endothelial Cells, Which Play Roles in Latency Establishment

Abstract: The DNA damage response (DDR) that evolved to repair host cell DNA damage also recognizes viral DNA entering the nucleus during infections. Here, we investigated the modulation of DDR signaling during de novo infection of primary endothelial cells by Kaposi's sarcoma-associated herpesvirus (KSHV). Phosphorylation of representative DDR-associated proteins, such as ataxia telangiectasia mutated (ATM) and H2AX, was induced as early as 30 min (0.5 h) postinfection and persisted during in vitro KSHV latency. Phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 48 publications
5
72
0
Order By: Relevance
“…MHV68 induces ATM and H2AX phosphorylation, and infected cells exhibit additional DDR-related phosphorylation events during lytic replication in fibroblasts (20,22,(43)(44)(45). However, the kinetics of the MHV68-associated DDR and whether it is associated with p53 activation are not well defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MHV68 induces ATM and H2AX phosphorylation, and infected cells exhibit additional DDR-related phosphorylation events during lytic replication in fibroblasts (20,22,(43)(44)(45). However, the kinetics of the MHV68-associated DDR and whether it is associated with p53 activation are not well defined.…”
Section: Resultsmentioning
confidence: 99%
“…ATM inhibition also does not block ORF59 expression during induced KSHV reactivation (63). Given differential requirements for ATM in GHV replication (20,24,44,63,(67)(68)(69), it is reasonable to suggest that ATM is situationally required for viral replication, perhaps in terminally differentiated cell types. However, since p53 was stabilized and transcriptionally active early during infection, these findings do indicate that viral induction of a DDR can have consequences on the infected cell, especially activation of downstream effectors such as p53.…”
Section: Discussionmentioning
confidence: 99%
“…28 In fact, it has been reported recently that KSHV can activate the DNA damage response during de novo infection of primary endothelial cells and this plays a role in establishing latency. 51 More recently, it has been demonstrated that lytic reactivation of KSHV leads to activation of the ataxia telangiectasia mutated (ATM) and DNA-dependent protein kinase DNA damage response kinases. 52 Inhibition of ATM results in the reduction of overall levels of viral replication whereas inhibition of DNA-dependent protein kinase increases activation of ATM and leads to earlier viral release.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other DNA viruses, both human (Epstein-Barr virus [EBV] and Kaposi's sarcoma-associated herpesvirus [KSHV]), and rodent (mouse gammaherpesvirus 68 [MHV68]) gammaherpesviruses benefit from ATM in vitro. Specifically, ATM activity and expression facilitate EBV reactivation from transformed cell lines (8) and the establishment of KSHV latency in primary endothelial cell cultures (9). Further, ATM expression enhances MHV68 replication in primary macrophages, but not mouse embryonic fibroblasts (MEF), in vitro (10), indicating that ATM functions as a proviral host factor in the context of many infected cell types.…”
mentioning
confidence: 99%